Characterisations of a fibre optic dosimetry system for source tracking during HDR Brachytherapy. (January 2019) - Al Towairqi, M; Cutajar, D L; Braddock, T; Li, E; Wadi-Ramahi, S; Moftah, B; Rosenfeld, A B
Abstract: Brachytherapy is a complex treatment procedure where radioactive sources are inserted in or close to the tumours to destroy the cancerous cells. Due to the unique properties of scintillation plastic detectors, this study was aimed to characterise an innovative fibre optic dosimetry system as a quality assurance tool during HDR Brachytherapy. Scintillating plastic fibres with different scintillation lengths were prepared and then optically coupled to non-scintillating fibres for light transmission. A transimpedance photodiode amplifier was used to detect positional sensitivities of different fibre probes placed within a solid-water phantom at varying distances above an 192-Ir brachytherapy source located within the catheter. Monte Carlo simulation has validated the expected response of the scintillating plastic fibres for multiple dwell positions with demonstrating the variance of detector response with source location. It showed the ability of shorter scintillating fibre lengths to distinguish between varying source locations when the SNR maintained high. However, fully scintillating plastic fibre showed flat response for most dwell positions. The proposed system proved to be appropriate for further clinical investigations, such as simultaneous dose measurement, and providing 3D position reconstruction through in-vivo source tracking.